(−)-Epicatechin in vitro ameliorates erythrocyte protein carbonyl content in hypertensive patients: comparison with L-ascorbic acid. (26th May 2016) - Kumar, Navneet; Maurya, Pawan Kumar; Kant, Ruchi; Rizvi, Syed Ibrahim
Abstract: Context : Oxidative stress plays a key role in the patho-physiology of hypertension. (−)-Epicatechin has many important biological properties. Objective : The present study was undertaken to evaluate effect of (−)-epicatechin on protein carbonyl content in gender-based hypertensive patients and normal subjects. Methods : The study was carried out on 83 normal (male: 42; female: 41) and 62 hypertensive subjects (male: 32; female: 30). In vitro effect on (−)-epicatechin and L-ascorbic acid was estimated on protein carbonyl content. Results : Result showed a significant ( p  < 0.001) increase in protein carbonyl content in hypertensive patients but no gender-based difference was observed. (−)-epicatechin shows significant ( p  < 0.001) dose-dependent effect as compared to L-ascorbic acid, which is manifested as decrease in protein carbonyl content. Conclusion : We hypothesizes that a higher intake of (−)-epicatechin may provide protection against hypertension in males and females.